PENGARUH KEPEMIMPINAN, KOMPENSASI, MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KABUPATEN SEMARANG - Tiya Febriani, 10.05.51.0057; Murdiyanto, Agus (Students Journal of Economic and Management, 2014)
This study aims to analyze the influence of leadership on employee performance, to analyze the effect of compensation on employee performance, to analyze the effect of work motivation on employee performance Object of study in this paper is Semarang District Department of Public Works. This research uses purposive sampling method, taking 75 respondents with a significance level of 5%, the data used primary data, data analysis using quantitative and qualitative analysis that includes test validity, reliability test, multiple regression analysis, t test,F testand the coefficient of determination. The results of the study it can be concluded, Leadership has a positiveand significant influence on employee performance, compensation has a positive and significant impacton employee performance, work motivationhas apositive and significant impacton employee performanceKeywords: Leadership, Compensation, Work MotivationandEmployee Performance